The final act of Juliette Willoughby : a novel [large type] - Lloyd, Ellery (Harper Large Print, an imprint of HarperCollinsPublishers, 2024)
"Everybody knows that in 1938, runaway heiress artist Juliette Willoughby perished in an accidental studio fire in Paris, alongside her masterpiece Self Portrait As Sphinx. Fifty years later, two Cambridge art history students are confounded when they stumble across proof that the fire was no accident but something more sinister. What they uncover threatens the very foundation of Juliette’s aristocratic family and revives rumors of the infamous curse that has haunted the Willoughbys for generations. But what does their discovery mean? And how is it connected to a brutal murder in present-day Dubai? A tale of love and madness, obsession and revenge, The Final Act of Juliette Willoughby unravels the riddle posed by a Sphinx who refuses to reveal her secrets...." --